Fallopian tube autoamputation after acute large endometrioma torsion - Luay Ibrahim Abu Atileh; Nouf Moh'd Khalifeh (Wolters Kluwer Medknow Publications, 2022)
Adnexal torsion is the fifth most common gynecological emergency. However, endometrioma torsion is a very rare entity due to the associated pelvic adhesions. A 26-year-old woman presented to the emergency department complaining of acute lower abdominal pain for the past 6 h. Physical examination showed localized left iliac fossa tenderness. Ultrasound showed a 13 cm endometrioma with a normal color Doppler. Laparoscopy revealed a 13 cm large endometrioma arising from the left ovary. The left Fallopian tube was amputated at its attachment to the left cornua. Reconstruction of the ovary was done and the specimen was retrieved through the umbilicus inside a bag. Autoamputation of the Fallopian tube alone, although very rare, is typically associated with a preceding torsion. It is critical to be aware of adnexal torsion, as it can have implications for future fertility. Therefore, laparoscopic detorsion and cystectomy are the gold standard management.